Intrinsically Stable Charged Domain Walls in Molecular Ferroelectric Thin Films - Xin Li; Cheng Li; Linming Zhou; Xiangwei Guo; Yuhui Huang; Hui Zhang; Shurong Dong; Yongjun Wu; Zijian Hong (Advanced Electronic Materials)
Abstract Charged domain walls in ferroelectrics hold great promise for applications in ferroelectric random‐access memory (FeRAM), with advantages such as low energy consumption, high density, and non‐destructive operation. Due to the mechanical compatibility condition, the neutral domain walls are dominant in traditional ferroelectric thin films. Herein, using phase‐field simulations, the formation of intrinsically stable charged domain walls (CDWs) in the molecular ferroelectric films is demonstrated, which can be mainly attributed to the small mechanical stiffness. The switching kinetics are further investigated for the CDWs, showing a lower switching barrier as compared to the neutral counterparts. Moreover, it is indicated that increasing the compressive misfit strain can lead to prolonged switching time, with a significantly increased switching energy barrier. These findings pave the way for the potential applications of metal‐free organic ferroelectric materials in FeRAM devices.